The Effect of Executive Stock Option Listing on the Underlying Stock Return Volatility, Bid-Ask Spread and Trading Volume - Kaivolahti, Sami (My University, 2008)
The introduction of new stock options has uncertain impacts on the characteristics of the underlying stock. This thesis examines how Finnish executive stock option listings affect the underlying stocks’ return volatility, bid-ask spread and trading volume. Hypotheses H1 and H2 of the theses imply that both raw and abnormal return volatilities are lower after executive stock option listings. Hypothesis H3 states that bid-ask spread is lower and the fourth hypothesis H4 is that trading volume is higher after executive stock option listings. The thesis examines a time period between the years 1998 and 2005. During this period new executive stock options were listed for a total number of 59 Finnish stocks. After several adjustments 45 observations are included in the final sample. To test the hypotheses, this thesis applies a control group method. Each firm in the sample group is matched with a control firm within the same industrial sector and if possible within the same size sector. Should the groups behave differently, it can be stated that the executive stock option listings have an effect. The empirical tests of the thesis show that both raw and abnormal return volatilities as well as bid-ask spreads are lower after the executive stock option listings. The differences to the control group are however indistinguishable. Therefore executive stock option listings do not seem to affect neither the underlying stock volatility nor the bid-ask spread. When trading volume was examined, it was noticed that trading volume was significantly higher after the executive stock option listings. Also the difference to the control group was more considerable. Therefore executive stock option listings appeared to increase trading volume.
Keywords: executive stock option; stock return volatility; bid-ask spread; trading volume; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|